La objeción de conciencia a los tratamientos médicos en la NBA la negativa a recibir la vacuna contra el covid-19 por motivos ¿religiosos? = Conscientious objection to medical treatment in the NBA : the refusal to receive the covid-19 vaccine on religious grounds? - Valencia Candalija, Rafael (2022)
This paper tries to analyse the conscientious objection of two NBA basketball players to receiving the Covid-19 vaccine on religious grounds. Essentially, the aim is to examine in depth the reasons alleged by the athletes, in an attempt to determine whether they constitute sufficient grounds to support their refusal to be vaccinated, and thus to continue carrying out their work obligations in order to preserve their beliefs. To do so, it is necessary to review the NBA's own protocols and state and local public health provisions on mandatory vaccination, without forgetting the pronouncements on the subject issued by the Supreme Court of the United States.
El presente trabajo trata de analizar la objeción de conciencia de dos jugadores de baloncesto de la NBA a recibir la vacuna contra el Covid-19 por motivos religiosos. Esencialmente, se persigue profundizar en los motivos alegados por los deportistas, intentado determinar si constituyen base suficiente para sustentar la negativa a vacunarse, y con ello, a seguir desarrollando sus obligaciones laborales para preservar sus creencias Para ello, resulta necesario realizar un recorrido por los protocolos de la propia NBA y las disposiciones estatales y locales en materia de salud pública en torno a la obligatoriedad de la vacunación, sin olvidar los pronunciamientos sobre la materia emanados del Tribunal Supremo de los Estados Unidos.
Keywords: Conscientious Objection on religious grounds; Vaccine; Objeción conciencia por motivos religiosos; vacuna; Covid-19; NBA